Jumantik Education: Strategy Toward Malaria Elimination in the Resettlement Area of Osi Island, West Seram Regency - Salakory, Melianus; Que, Stela; Makulua, Izak Jakobis (KnE Social Sciences, 2024)
The Covid-19 pandemic, which has been global for 3 years, tends to have a domino effect in various aspects, such as individuals, groups, and countries. One of the causes of decreased immune system in the host is due to comorbid diseases suffered by the host (patients). Those at risk of Covid-19 may also be at risk of infectious diseases caused by viruses, parasites, and bacteria. In a pandemic situation like Covid-19, health behavior change education with a risk communication approach needs to be implemented in preventing, treating, and rehabilitating environmental stages of worm infection risk in the community of Osi Island hamlet. This education aims to increase public knowledge of potential health risks and threats. Thus, they can determine appropriate steps and actions to protect themselves from these issues. The method used is education with the project-based learning model, which combines lecture, discussion, and field practice methods. The target group is high school students of PGRI Pelita Jaya Seram Western Part. The achieved results are that the JUMANTIK cadres know about malaria-free health (cognitive), can collect trash (containers) from yards (psychomotor), do not allow stagnant water (affective), can drain water storage containers inside and around the house (psychomotor), can make simple mosquito traps using recycled materials, can sleep under mosquito nets (psychomotor), can observe larvae and pupae (psychomotor). Kyewords: Jumantik education, malaria elimination, Osi Island